2016
DOI: 10.1038/nnano.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot-loaded monofunctionalized DNA icosahedra for single-particle tracking of endocytic pathways

Abstract: Functionalization of quantum dots (QDs) with a single biomolecular tag using traditional approaches in bulk solution has met with limited success. DNA polyhedra consist of an internal void bounded by a well-defined three-dimensional structured surface. The void can house cargo and the surface can be functionalized with stoichiometric and spatial precision. Here, we show that monofunctionalized QDs can be achieved by encapsulating QDs inside DNA icosahedra and functionalizing the DNA shell with an endocytic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 46 publications
1
133
0
Order By: Relevance
“…Lys and FA are two main types of small molecules with excellent biocompatibility and are often used to modify nanomaterials. 40,41 To this end, apart from bulk MoS 2 , simply functionalized MoS 2 materials including Lys-and FA-modified MoS 2 were also synthesized using the same batch of bulk MoS 2 materials as additional controls alongside MoS 2 /GO nanocomposites. Meanwhile, the same batch of GO sheets used for MoS 2 hybrid was also used here for comparison.…”
Section: Synthesis and Characterization Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
“…Lys and FA are two main types of small molecules with excellent biocompatibility and are often used to modify nanomaterials. 40,41 To this end, apart from bulk MoS 2 , simply functionalized MoS 2 materials including Lys-and FA-modified MoS 2 were also synthesized using the same batch of bulk MoS 2 materials as additional controls alongside MoS 2 /GO nanocomposites. Meanwhile, the same batch of GO sheets used for MoS 2 hybrid was also used here for comparison.…”
Section: Synthesis and Characterization Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
“…QDs possess unique size-dependent photo luminescent properties due to the quantum confinement effect [124][125][126]. They produce bright emissions spanning the visible and infrared spectrum when excited by high-energy photons.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Simulations and experiments have indicated that the DNA icosahedron has an effective in-circle diameter of ∼2.8 nm at its triangular face (13,15). This implies that small thiols with diameter ∼1 nm can rapidly permeate the DNA icosahedron and initiate thiol-disulfide exchange to release 4-MU.…”
Section: Significancementioning
confidence: 99%
“…DNA polyhedra have controllable dimensions and are addressable with single-nucleotide precision, with the Turberfield tetrahedron (12) and a DNA icosahedron being the most widely used for biological applications (13,14). Particularly, the DNA icosahedron has been used to encapsulate diverse cargo such as gold nanoparticles, fluorescent polymers (15,16), and quantum dots for bioimaging (13).…”
mentioning
confidence: 99%